Relationship between creatinine–cystatin C ratio and all-cause mortality in hospitalized patients with COVID-19: A prospective study in China - Wu, Dong; Cao, Jiahao; Lin, Yiyan; Chen, Xiaoer; Long, Bingyu; Huang, Bangxiao; Liu, Gege; Fu, Xiaofang; Wu, Bin; Huang, Dan; Zhang, Yuanli; Wang, Duolao; et al. (Heliyon, 2024)
This study was conducted to investigate whether baseline creatinine–cystatin C ratio is associated with all-cause mortality in adult Chinese patients hospitalized with coronavirus disease 2019. This study included 933 patients with coronavirus disease 2019 who were admitted to The Affiliated Hospital of Guangdong Medical University between December 2022 and March 2023. All-cause mortality was determined by telephone follow-up after 28 days. Multivariate Cox proportional risk models were used to investigate the relationship between baseline creatinine–cystatin C ratio and all-cause mortality. Restricted cubic spline and two-piecewise Cox proportional hazards risk models were used to identify non-linear correlations. Of the 933 patients, 128 died during the 28 days follow-up. The restricted cubic spline analysis of hospitalized patients with coronavirus disease 2019 revealed an L-shaped association between baseline creatinine–cystatin C ratio and all-cause mortality, with a threshold creatinine–cystatin C ratio of ≤0.93 predicting all-cause mortality. Specifically, a baseline creatinine–cystatin C ratio below this threshold value was negatively correlated with mortality (hazard ratio 0.12, 95 % confidence interval 0.03–0.48), but a creatinine–cystatin C ratio >0.93 was not correlated with mortality (hazard ratio 1.29, 95 % confidence interval 0.65–2.55). In Chinese adult patients hospitalized with coronavirus disease 2019, an L-shaped relationship was observed between the baseline creatinine–cystatin C ratio and all-cause mortality.